Attachment to Peers and Delinquency - Rahman, Zulaiha A Rahman (Universiti Sains Malaysia, 2006)
The present research was designed to investigate the relationship between peer attachment and delinquency. The samples of this study are incarcerated youth from Henry Gurney School, Batu Gajah, Perak and Henry Gurney School, Ayer Keroh, Malacca and consisted of 32 female and 141 male juveniles that are randomly selected. A set of questionnaire was used to measure peer attachment and delinquency among these juveniles. The peer attachment questionnaire is a simplified version of the Inventory of Parent and Peer Attachment (IPP A: Armsden & Greenberg, 1987). It comprised 25 items divided into three main scales, i.e. trust, communication and alienation. The self-reported delinquency questionnaire comprised 29 items related on individual involvement in delinquent activities. The hypotheses were tested by using the Pearson product moment correlation and t-test analysis using the SPSS/PC and package for statistical analysis. The results indicated that there is no significant correlation between peer attachment and delinquency in juveniles. However, a significant negative correlation exists between subscale of peer attachment quality of communication and delinquency in male juveniles. In term of peer attachment quality, the present study found a correlation between subscale of peer attachment quality of trust and subscale of peer attachment quality of communication in juveniles. It is interesting to note that, male juveniles tend to show higher mean value of delinquency than female juveniles. Regarding involvement of juveniles in group, juveniles who reported involve in group showed higher mean value of delinquency compared to juveniles who did not involved in any group.